Social Studies Students’ Motivation in Online Learning during COVID-19 Pandemic - Pedroso, John Erwin Prado; John Patrick B. Magbato; Vivienne Louise B. Lopez; Joseph James P. Llorico (RADINKA JAYA UTAMA PUBLISHER, 2022)
This study described the experiences of social studies students as well as how they managed to stay inclined to learn given the struggles, they faced during the COVID-19 pandemic. Also, it looked at how social studies students have faced challenges but are still actively pursuing their own dreams during the pandemic. This research employed a qualitative-narrative approach, involving five (5) social studies students. As data collection techniques, students were asked to write narratively using Gibbs reflective cycle. The findings revealed that students' motivation to continue learning during the COVID-19 pandemic was divided into three main themes, each with its own set of categories and subcategories. The three themes and categories described were: (a) personal, with categories of challenges, self-determination, satisfaction and religious commitment; (b) social, with categories of relationships, inspiration, and well-being; and (c) environmental, with categories of breaking in/conditioning and amenities. The themes and categories showed that these social studies students got their inspiration to learn during the pandemic. According to the findings, these students were intrinsically and extrinsically motivated and dedicated to their studies. The majority of these students were spurred by their individual goals, not by a controlled motive, an incentive, a consequence, or a regulation. This study proposes that students be prepared to be more resilient and to build the ability to be hopeful and motivated to succeed and transcend any of life's hardships by defining how they achieved to motivate themselves.